Inhibition of MicroRNA-92a Improved Erectile Dysfunction in Streptozotocin-Induced Diabetic Rats via Suppressing Oxidative Stress and Endothelial Dysfunction - Zhe Tang; Jingyu Song; Zhe Yu; Kai Cui; Yajun Ruan; Yang Liu; Tao Wang; Shaogang Wang; Jihong Liu; Jun Yang (The World Journal of Men's Health, 2023)
Purpose: To determine whether microRNA could be a therapy target of erectile dysfunction (ED) and the underlying mechanisms. Materials and Methods: Eight-week-old fasting male SD rats were intraperitoneally injected with streptozotocin to construct diabetic rat models. Diabetic ED rats were treated with miRNA-92a inhibitor. The cavernous nerves were electrically stimulated to measure the intracavernous pressure and mean arterial pressure of rats in each group. After the detection, the penile cavernous tissues are properly stored for subsequent experiments. Rat aortic endothelial cells were used in in vitro studies. Results:The expression of miR-92a was significantly increased in the corpus cavernosum of Streptozocin (STZ)-induced diabetic rats and injection of miR-92a antagomir into the corpus cavernosum of diabetic rats significantly increased eNOS/NO/ cGMP signaling pathway activities, cavernous endothelial cell proliferation, endothelial cell-cell junction protein expression and decreased the levels of oxidative stress. These changes restored erectile function in STZ-induced diabetic rats. Moreover, in vitro study demonstrated that the miR-92a expression increased significantly in endothelial cells treated with high glucose, inhibiting AMPK/eNOS and AMPK/Nrf2/HO-1 signaling pathways in rat aortic endothelial cells via targeting Prkaa2, causing endothelial dysfunction and overactive oxidative stress, miR-92a inhibitor can improve the above parameters. Conclusions: miRNA-92a inhibitor could exert an inhibition role on oxidative stress and endothelial dysfunction to improve diabetic ED effectively.